Needs Analysis of Interactive Multimedia Teaching Materials on Alternative Energy Content to Facilitate Students' Concept Mastery and Technology Literacy - Qurroh Ayun Aunillah; Asrizal Asrizal; Hidayati Hidayati; Dea Stivani Suherman (Jurnal Penelitian Pembelajaran Fisika, 2026)
One of the abilities that 21st-century students must possess is technology literacy. This study aims to analyze students' concept mastery and technology literacy on the alternative energy topic.Based on observations at SMA N 4 Solok, several issues were found in physics learning, namely problems with the alternative energy topic, low student learning outcomes, and low student technology literacy. To respond to this, a needs analysis stage was carried out using a Research and Development (R&D) approach, utilizing the Hannafin and Peck model.Data was collected through a questionnaire given to 35 students and 1 physics teacher, a discourse test to reveal issues with the alternative energy topic and technology literacy, and mid-semester exam results to assess concept mastery.The analysis results indicate that teaching materials are not optimally supporting ICT-based learning, and students' scores are still below the Minimum Competency Criteria (KKM). These findings highlight the need to develop innovative, interactive, and contextual multimedia teaching materials to facilitate more meaningful physics learning.